Biologiese droging van Pinus radiata (D. Don)-bome - Visser, J. J.(Johannes Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (Ph.D. (Houtkunde)) -- Universiteit van Stellenbosch, 1982.